Normal giants? Temporal and latitudinal shifts of Palaeozoic marine invertebrate gigantism and global change. (23rd October 2014) - Klug, Christian; De Baets, Kenneth; Kröger, Björn; Bell, Mark A.; Korn, Dieter; Payne, Jonathan L.
Abstract : During and after the Cambrian explosion, very large marine invertebrate species have evolved in several groups. Gigantism in Carboniferous land invertebrates has been explained by a peak in atmospheric oxygen concentrations, but Palaeozoic marine invertebrate gigantism has not been studied empirically and explained comprehensively. By quantifying the spatiotemporal distribution of the largest representatives of some of the major marine invertebrate clades (orthoconic cephalopods, ammonoids, trilobites, marine eurypterids), we assessed possible links between environmental parameters (atmospheric or oceanic oxygen concentrations, ocean water temperature or sea level) and maximum body size, but we could not find a straightforward relationship between both. Nevertheless, marine invertebrate gigantism within these groups was temporally concentrated within intervals of high taxonomic diversity (Ordovician, Devonian) and spatially correlated with latitudes of high occurrence frequency. Regardless of whether temporal and spatial variation in sampled diversity and occurrence frequency reflect true biological patterns or sampling controls, we find no evidence that the occurrences of giants in these groups were controlled by optimal conditions other than those that controlled the group as a whole; if these conditions shift latitudinally, occurrences of giants will shift as well. It is tempting to attribute these shifts to contemporary changes in temperature, oxygen concentrations in the atmosphere and the oceans as well as global palaeogeography over time, but further collection‐based studies are necessary on finer stratigraphic and phylogenetic resolution to corroborate such hypotheses and rule out sampling or collection biases.